Bahasa Inggris - A. M. Shofiyuddin; B. Zahro (Jurnal Manajemen Indonesia, 2025)
This study investigates the influence of religiosity on leadership and organizational performance in MSMEs. The research objects are MSMEs in Pekalongan City. The objectives of this study are to identify the influence of religiosity on leadership within the MSME context, analyze how religiosity-based leadership affects organizational performance in MSMEs, and provide practical recommendations for MSME leaders to integrate religious values into their leadership strategies to improve organizational performance. The sample size consists of 378 respondents. The analysis tool used PLS-SEM, with data collected via a questionnaire using a Likert scale of 1-5. The findings indicate that religiosity has a significant impact on leadership and organizational performance in MSMEs in Pekalongan City. Leadership plays a crucial role as a mediator between religiosity and organizational performance. Applying religiosity in leadership is essential for MSME actors, especially in Pekalongan, as it can improve MSME organizational performance.